THE INFLUENCE OF DIGITAL BRANDING ON BRAND AWARENESS AND PURCHASE DECISIONS AMONG MSMES IN PALEMBANG: A CASE STUDY ON ZANAIA ACRYLIC - RM Chairil Andri; Hadi Wijaya (Faculty of Economics and Business, Universitas Klabat, 2023)
Digital branding has become a necessity in the contemporary business landscape. These branding efforts often involve leveraging social media marketing and influencer marketing techniques to enhance brand awareness and drive product sales. This study aims to investigate the role of digital branding strategies at ZANAIA Acrylic Palembang in influencing brand awareness and purchase decisions for MSMEs' products or services. The independent variables encompass social media marketing and influencer marketing, while brand awareness acts as the intervening or mediating variable, and purchasing decisions represent the dependent variable. Primary data was collected using a questionnaire as the research instrument and analyzed using SPSS. The study involved a total sample of 100 respondents in Palembang City. The anticipated results of this research are expected to contribute valuable insights and serve as a reference for other SMMEs in formulating effective business strategies, targeting consumers, and optimizing their profits. Keywords: Digital Branding, Social Media Marketing, Influencer Marketing, Brand Awareness, Purchasing Decision